DEVELOPING ENGLISH SPEAKING MATERIAL FOR THE TENTH GRADE STUDENTS OF ACCOUNTING PROGRAM AT SMK NEGERI 1 SIDIKALANG - Desla Paramita Tumangger; Rika; Maya Oktora (Universitas Negeri Medan, 2024)
This research was aimed to develop English speaking materials for the students of Accounting program at SMK Negeri 1 Sidikalang especially the tenth grade. The research was conducted by Research and Development (R & D) design through four phases; Evaluation and Need Analysis, Material Development, Material Validation and Revision and Final Product. It was conducted at SMK Negeri 1 Sidikalang. The date were gathered by administering interview to English teacher and distributing questionnaire to 10 students to get the student’s needs. The result of questionnaire showed that the relevance of existing Speaking material with Accounting major just 35 % (less relevant) and 90 % of the students need the relevance English speaking material with their major and related to work situation. The interview and questionnaire results prove that the students need English Speaking materials which contain the appropriate knowledge or topic with the syllabus, student’s level and major. The material developed into 3 units based on the basic competence on syllabus; Congratulating and Complimenting, Expressing Intention, and Giving Announcement. The product of English speaking material validated by two experts, lecturer and English teacher. The result of experts’ judgment is 89.5 and it belongs to good category. The experts’ validation shows that the materials are appropriate and recommended to be used for students of Accounting program especially in SMK Negeri 1 Sidikalang.